RELIGIOUS CULTURE DEVELOPMENT STRATEGY FOR SHAPING CHARACTER OF STUDENTS - Devi Wangsa; Fadhilah Khairiyah; Murali Murali; Haidir Haidir (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Religious culture that applied in schools is an attempt to shape learners noble habits. As the purpose of national education, students strived to develop his potential to have the spiritual power and noble character. So the strategy of religious culture development is important to be applied at school that students have noble character and are able to be the successor nation that Moslem minded. The focus of this study is how the program of religious culture development, the implementation of development religious culture strategies and how it impacts on students character at MAN Pematangsiantar and SMK Negeri 1 Pematangsiantar. The study uses a qualitative approach with case studies and drafts multi-case. The collection of data obtained through in-depth interviews, observation, and documentation study. The informer of research: is a lecturer of Islamic education, lecturer of guidance and counseling, and students. The research used purposive sampling with snowball sampling technique. Checking the validity of the data by using the member check and proceed with triangulation techniques. The result indicate that (1) the development of religious culture program in MAN Pematangsiantar and SMK Negeri 1 Pematangsiantar include: allocate one hour of Islamic Education lesson at the zoom meeting, and reading asmaul husna. (2) the implementation of development religious culture strategies is done through the provision explanations, involving students organizations, provide reinforcement behavior, control assessment, modeling, and the use of symbols, (3) the impact of religious culture development on student's character including discipline, religious, curiosity, honest and independent character.